2014
DOI: 10.2478/10004-1254-65-2014-2570
|View full text |Cite
|
Sign up to set email alerts
|

A survey of professional satisfaction among anaesthesiologists in Serbia

Abstract: We would like to briefly address our recent findings regarding professional satisfaction among anaesthesiologists in Serbia. It is generally wellknown among physicians that the life expectancy of anaesthesiologists is smaller than in other specialties (1). Many resort to the use of cigarettes, drugs, alcohol (2). The number of suicides among anaesthesiologists is significantly larger in comparison with other physicians (3, 4). Needless to say, the level of professional satisfaction is in a direct link with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Five were presented only as conference abstracts and two were letters. The topics covered were burnout (n = 8) [43–50]; depression (n = 2) [51, 52]; occupational stress (n = 3) [53–55]; substance abuse (n = 1) [51]; and well‐being (n = 1) [56]. The studies that gave a prevalence for burnout in samples of anaesthetists reported proportions of 44% [44] to 78% [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five were presented only as conference abstracts and two were letters. The topics covered were burnout (n = 8) [43–50]; depression (n = 2) [51, 52]; occupational stress (n = 3) [53–55]; substance abuse (n = 1) [51]; and well‐being (n = 1) [56]. The studies that gave a prevalence for burnout in samples of anaesthetists reported proportions of 44% [44] to 78% [50].…”
Section: Resultsmentioning
confidence: 99%
“…Five were presented only as conference abstracts and two were letters. The topics covered were burnout (n = 8) [43][44][45][46][47][48][49][50]; depression (n = 2) [51,52]; occupational stress (n = 3)…”
Section: Surveys Related To Other Mental Health Conditions (Category C)mentioning
confidence: 99%